The Factors Related With Exclusive Breastfeeding for Working Mothers at Somba Opu Gowa Community Health Center in 2020: Faktor-Faktor yang Berhubungan dengan Pemberian ASI Esklusif Bagi Ibu Bekerja di Wilayah Kerja Puskesmas Somba Opu Gowa Tahun 2020 - Triananinsi, Nurhidayat; Hasriani Saleng; Mudyawati Kamaruddin; Sutrani Syarif; Ani T Prianti; Noveppy Cahya Permatasari (Jurnal Midwifery, 2024)
The purpose of this research was to identify the factors related to the exclusive breastfeeding for mothers’working at Somba Opu Gowa Community Health Center in 2020. The type of research used analytic survey. The population and sample were 67 in this research of 31 working mothers who were immunized for their infants aged 7-24 months at Somba Opu Gowa Community Health Center, which met the inclusion and exclusion criteria on April 16 - June 24, 2020 were taken by using purposive sampling technique by using chi- square with a value of α = 0.05. The results of the analysis showed that there was no relationship between education and exclusive breastfeeding for working mothers with a value of p = 1,000> α (0.5) so Ho was accepted and Ha was rejected. There was the relationship between the level of knowledge and exclusive breastfeeding for working mothers with a value of p = workplace policy with exclusive breastfeeding for working mothers with a value of p = 0.000<α (0.05) so Ho was rejected and Ha was accepted. There is a relationship between Workplace Policy and Exclusive Breastfeeding for working mothers with a value of p =0.032 <α (0.5) so Ho was rejected and Ha was accepted.